Anti-proliferative activity-guided isolation of clerodermic acid from Salvia nemorosa L.: Geno/cytotoxicity and hypoxia-mediated mechanism of action. (October 2018) - Bahadori, Mir Babak; Eskandani, Morteza; De Mieri, Maria; Hamburger, Matthias; Nazemiyeh, Hossein
Abstract: The adaptation of solid tumors to the low oxygen/nutrient environment is mediated by the pivotal transcription role of hypoxia-inducible factor-1 (HIF-1). Thus, the HIF-1 and its subunits have been considered to be hopeful anti-cancer targets. Various natural compounds were reported to persuade cell cytotoxicity through targeting and downregulation of the HIF-1. The genus Salvia is a rich source of bioactive terpenoids which show promising anti-cancer activities. Here, the identification of natural anti-proliferative compound targeting the HIF-1α expression was reported. A bioassay-guided isolation was employed for the discovery of natural anti-proliferative compounds from Salvia extracts using MTT assay against A549 cells. In this direction, clerodermic acid (CDA) as a potent cytotoxic compound was purified from Salvia nemorosa and identified using 1D and 2D NMR analysis. Results indicated that CDA has anti-proliferation activity (IC50 value of 35 μg/mL) which was confirmed by genotoxicity and apoptosis detection analyses. The quantitative qPCR analysis showed that the expression level of HIF-1 alpha was strongly inhibited in the hypoxic cells treated with CDA compared to the untreated cells tolerated hypoxia. Findings exhibited that S. nemorosa and clerodermic acid have significant potential for reducing HIF-1α expression and could be considered for further studies for cancer therapy.